From Sick Man of Europe to Economic Superstar: Germany's Resurgent Economy - Christian Dustmann; Bernd Fitzenberger; Uta Schönberg; Alexandra Spitz-Oener (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2014)
The astonishing transformation of the German economy from the 'sick man of Europe' to a lean and highly competitive economy is predominantly due to the decentralisation of wage bargaining rather than government labour market reforms.
Keywords: 330; wage structure; competitiveness; wage bargaining; labour market reforms; Germany